AN INVERSE MODELING APPROACH FOR THE CHARACTERIZATION OF UNSATURATED WATER FLOW IN AN ORGANIC FOREST FLOOR - Kosugi K.; Mori K.; Yasuda H. (My University, 2001)
Although the retention of rain-water by a forest floor consisting of vegetation litter has large hydrological and geomorphological effects in a forested catchment, its physical processes have not yet been clarified. For the purpose of examining the applicability of Richards equation to unsaturated water flow in forest floor, results of artificial rainfall experiments were analyzed by the inverse method. Forest floor samples were collected from a beech-stand, an oak-stand, a cedar-stand and a mixed-stand of coniferous and broad-leaved trees. The samples were piled up to make long columns of 20.6cm in inner diameter and about 50cm in height, with which step-wise drainage experiments and random-rainfall experiments were conducted. Parameters in water retention and hydraulic conductivity functions were optimized by comparing the observed versus computed discharge rates for the step-wise drainage experiments. The derived retention and conductivity functions succeeded to reproduce the observed drainage hydrographs during the random-rainfall experiments, indicating that Richards equation can describe the unsaturated water flow in all the forest floor studied. The derived retention functions suggested that the forest floors have a small water capacity except for the very wet range where the matric pressure head, ψ, is greater than -5cm. The conductivity functions of all the forest floors exhibited a sharp drop in the range of ψ>-5cm, and decreased gradually as ψ decreased further. The forest floors at the beech-stand and the oak-stand had larger water capacities and smaller conductivity values than the forest floors at the cedar-stand and the mixed-stand. Consequently, the discharge hydrographs of the forest floors at the beech-stand and the oak-stand were characterized by more gradual responses to rainfall than the forest floors at the cedar-stand and the mixed-stand. Overall, the proposed inverse technique was effective to characterize the unsaturated water flow in forest floor.
Keywords: FOREST FLOOR; ORGANIC SOIL LAYERS; WATER RETENTION; HYDRAULIC CONDUCTIVITY; INVERSE METHOD